Childhood Innocence for Settler Children: Disrupting Colonialism and Innocence in Early Childhood Curriculum. Issue 2 (2nd April 2020) - Templeton, Tran Nguyen; Cheruvu, Ranita
ABSTRACT: This article explores the challenges of rewriting prescriptive early childhood curriculum wherein settler colonialism and childhood innocence as a discourse reinforce one another. We attend to two primary ideas: 1) that the presence of settler colonialism pervades everyday practices in the early years, and 2) early childhood curriculum maintains young children's innocence vis-a-vis the regulation of their knowledge of colonial violence and Indigenous dispossession. By examining the curricular revisions of one pre-service teacher, we highlight the tensions that educators may undergo in negotiating the violence of U.S. settler colonialism within classrooms with young children.